Automated Remote Pulse Oximetry System (ARPOS) - Pireh Pirzada; David Morrison; Gayle Doherty; Devesh Dhasmana; David Harris-Birtill (Sensors, 2022)
Current methods of measuring heart rate (HR) and oxygen levels (<semantics>SPO2</semantics>) require physical contact, are individualised, and for accurate oxygen levels may also require a blood test. No-touch or non-invasive technologies are not currently commercially available for use in healthcare settings. To date, there has been no assessment of a system that measures HR and <semantics>SPO2</semantics> using commercial off-the-shelf camera technology that utilises R, G, B, and IR data. Moreover, no formal remote photoplethysmography studies have been performed in real-life scenarios with participants at home with different demographic characteristics. This novel study addresses all these objectives by developing, optimising, and evaluating a system that measures the HR and <semantics>SPO2</semantics> of 40 participants. HR and <semantics>SPO2</semantics> are determined by measuring the frequencies from different wavelength band regions using FFT and radiometric measurements after pre-processing face regions of interest (forehead, lips, and cheeks) from colour, IR, and depth data. Detrending, interpolating, hamming, and normalising the signal with FastICA produced the lowest RMSE of 7.8 for HR with the r-correlation value of 0.85 and RMSE 2.3 for <semantics>SPO2</semantics>. This novel system could be used in several critical care settings, including in care homes and in hospitals and prompt clinical intervention as required.